Seasonal dynamics of flowering of Calluna vulgaris (L.) Hull and its cultivars in conditions of Kyiv regarding to peculiarities of the flower structure - Kuznetsova, Maria (ScienceRise: Biological Science, 2019)
The aim of our study was to research the connection between the flower structure and the duration of flowering of Calluna vulgaris (L.) Hull and its cultivars. Our tasks were to investigate the flower structure of bud bloomers and double-flowered Calluna vulgaris (L.) Hull cultivars, to compare it with the structure of C. vulgaris flower; to analyze the data of phenological observations of C. vulgaris and its 10 cultivars flowering phase during 2015–2018. The methods were phenological observations and microscopic examinations. Results. Common features for C. vulgaris and cultivars concerning to their flowering are racemose inflorescences, an arrangement of flowers, acropetal succession. The flower structure of ‘Dirry’, ‘Mullion’, ‘Golden Carpet’, ‘Winter Red’ is similar to that of C. Vulgaris. Among this group, ‘Winter Red’ finishes blooming the first and ‘Dirry’ is the last due to its compound inflorescence. An increased number of petals, full sterility and long flowering period characterize flowers of double-flowered cultivars. Bud bloomers ‘Alicia’, ‘Bonita’ belong to f. diplocalyx Jansen. They are characterized by different flowering periods. ‘Alicia’ blooms the longest (85±7 days) among investigated C. vulgaris cultivars and ‘Bonita’ blooms about 53 days. Conclusions. C. vulgaris cultivars that have the same flower structure as species begin to bloom, as well as common heather, in the third decade of July. The duration of C. vulgaris cultivars flowering period depends also on the peculiarities of the inflorescence structure. Therefore, in order to predict the duration of cultivars flowering, it is necessary to study the features of their inflorescences structure. Double-flowered cultivars are worth to be used more often in gardening due to their high decorativeness and long flowering period. The issue of preserving the color of bud bloomers flowers needs further research. When using the cultivars of C. vulgaris with different types of flowers and duration of flowering, we can create landscapes of high and long decorative features